2005
DOI: 10.17660/actahortic.2005.678.23
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Pharmaceutical Development of Essential Oil From Hyptis Suaveolens

Abstract: Volatile oil distilled from the overground part of Hyptis suaveolens was preliminary quality controlled by GC. The antibacterial activity of this volatile oil was tested against various kinds of bacteria and fungi that caused dermatological diseases by agar dilution method. It was found that the volatile oil from H. suaveolens inhibited certain bacteria and fungi. A number of cream bases were prepared and evaluated for the satisfactory physical properties and stability. The creams containing 30% w/w of oil in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
2
3
0
1
Order By: Relevance
“…The clear liquid oil with physical appearance of pale yellow is same with all previous work. Essential oil yield of about 0.4-0.6ml/ kg (equivalent to 0.1%) got in this studies is same with the work of Raizada 19 who got a percentage yield of 0.1 from the same plant, never the less it is low compared with the work of the following researchers; Iwalokun et al 20 a percentage yield of 0.31 and Okonogi et al 21 percentage yield of 0.21; The difference in percentage yield could be due to the moisture level of the leaves and the chemotypic profile of the Hyptis suaveolens strains analysed. 20 Latitude, altitude, soil composition, climate and genetic composition are factors that have been implicated for chemotype variations in Hyptis suaveolens and other species of Hyptis as well as other aromatic herbs belonging to the Lamiaceae family.…”
Section: Discussionsupporting
confidence: 86%
“…The clear liquid oil with physical appearance of pale yellow is same with all previous work. Essential oil yield of about 0.4-0.6ml/ kg (equivalent to 0.1%) got in this studies is same with the work of Raizada 19 who got a percentage yield of 0.1 from the same plant, never the less it is low compared with the work of the following researchers; Iwalokun et al 20 a percentage yield of 0.31 and Okonogi et al 21 percentage yield of 0.21; The difference in percentage yield could be due to the moisture level of the leaves and the chemotypic profile of the Hyptis suaveolens strains analysed. 20 Latitude, altitude, soil composition, climate and genetic composition are factors that have been implicated for chemotype variations in Hyptis suaveolens and other species of Hyptis as well as other aromatic herbs belonging to the Lamiaceae family.…”
Section: Discussionsupporting
confidence: 86%
“…The clear liquid oil with physical appearance of pale yellow is same with all previous works. Essential oil yield of about 0.4-0.6ml/ kg (equivalent to 0.1%) got in this studies is same with the work of Raizada 17 who got a percentage yield of 0.1 from the same plant, never the less it is low compared with the work of the following researchers; Iwalokun et al, 18 a percentage yield of 0.31 and Okonogi et al, 19 percentage yield of 0.21; The difference in percentage yield could be due to the moisture level of the leaves and the chemotypic profile of the Hyptissuaveolens strains analysed. Latitude, altitude, soil composition, climate and genetic composition are factors that have been implicated for chemotype variations in Hyptissuaveolens and other species of Hyptis as well as other aromatic herbs belonging to the Lamiaceae family.…”
Section: Discussionsupporting
confidence: 86%
“…The results also showed that leaf and root extracts from H. suaveolens can be used effectively to inhibit the growth of fungi associated with postharvest bio-deterioration of cabbage. Thus, H. suaveolens possesses antifungal properties as reported by Okonogi et al (2005) and Sharma et al (2013).…”
Section: Discussionmentioning
confidence: 57%